2020
DOI: 10.2196/23939
|View full text |Cite
|
Sign up to set email alerts
|

Predicted Influences of Artificial Intelligence on the Domains of Nursing: Scoping Review

Abstract: Background: Artificial intelligence (AI) is set to transform the health system, yet little research to date has explored its influence on nurses-the largest group of health professionals. Furthermore, there has been little discussion on how AI will influence the experience of person-centered compassionate care for patients, families, and caregivers. Objective: This review aims to summarize the extant literature on the emerging trends in health technologies powered by AI and their implications on the following … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
83
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 123 publications
3
83
0
2
Order By: Relevance
“…Recent systematic and scoping reviews on the application of AI in nursing research (as well as in practice and emerging trends), covering original research published until October 2019, identified papers listed in medical and multidisciplinary databases. These included studies focused on machine learning (ML) methods, such as deep learning [ 2 ], or on health technologies that incorporate AI approaches themselves, such as robots or clinical decision support systems [ 3 ]. Various application scenarios have been identified, including clinical or organizational outcomes (eg, falls), admission decisions in emergency medicine, high-definition image recognition, as well as socially assistive robots or health care assistant chatbots [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent systematic and scoping reviews on the application of AI in nursing research (as well as in practice and emerging trends), covering original research published until October 2019, identified papers listed in medical and multidisciplinary databases. These included studies focused on machine learning (ML) methods, such as deep learning [ 2 ], or on health technologies that incorporate AI approaches themselves, such as robots or clinical decision support systems [ 3 ]. Various application scenarios have been identified, including clinical or organizational outcomes (eg, falls), admission decisions in emergency medicine, high-definition image recognition, as well as socially assistive robots or health care assistant chatbots [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although many of the purported potential benefits of AI (eg, improved patient outcomes, streamlined workflow, improved efficiency) have yet to be fully shown in nursing research, 6 it is inevitable that AI technologies will be used more regularly to support and extend nurses' cognitive, decision making, and potentially labor functions. 15 These opportunities bring new and dynamic practice considerations for nursing and interprofessional expertise.…”
Section: Investigate Artificial Intelligence In Nursing Practicementioning
confidence: 99%
“…The development and application to nursing of systems based on AI are still in their infancy. But preliminary evidence suggests virtual chatbots could play a part in streamlining communication with patients, and robots could increase the emotional and social support patients receive from nurses, while acknowledging inherent challenges such as data privacy, ethics, and cost effectiveness 6…”
mentioning
confidence: 99%
“…These AI and ML technologies require to instruct patients to ensure that patient does not mistake intelligent system for a human-driven application. Furthermore, consent of applications obtained outside the medical environment rises thorny concerns [ 68 ]. AI is susceptible to misjudgment and incorrect risks.…”
Section: Ethical Concern Of Artificial Intelligence and Machine Learning Based Robotic Therapymentioning
confidence: 99%